Analisa Kinerja Jalanan Much. Prabu Mangkunegara Palembang - M Helmi Ananda Saputra; Pujiono T; Ramadhani Ramadhani (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This research aims to analyze the performance of Jalan Much. Prabu Mangkunegara in Palembang, focusing on traffic volume, road capacity, degree of saturation, and level of service. The research scope encompasses a 100-meter road segment, with observations conducted during peak hours (07:00–12:00 Western Indonesia Time). The research methodology includes field surveys to collect primary data such as vehicle volume, side friction, and road geometry, alongside data analysis based on the 1997 Indonesian Road Capacity Manual (Manual Kapasitas Jalan Indonesia/MKJI). The results indicate that the highest traffic volume occurred between 08:00–09:00 WIB, reaching 9,566.5 passenger car units per hour (pcu/hour). The degree of saturation (DS) reached 3.426, indicating a level of service "F" (very congested). Side friction was categorized as both "High" (H) and "Low" (L). The calculated road capacity was 2,791.53 pcu/hour. In conclusion, Jalan Much. Prabu Mangkunegara experiences severe congestion due to a vehicle volume that significantly exceeds its capacity.